Новые и малоизвестные поденки рода Baetis группы Rhodani (Ephemeroptera, Baetidae) из Средней Азии и Казахстана - Клюге, Н.Ю. (Вестник зоологии, 1982)
Two species of Baetidae mayfly family are described as new. Male imago of Baetis oreophilus sp. nov. is characterized by elongated forcepses of last joint; its n y m p h IS similar to B. rhodani, with two hairs on each claw and spines on front and hind mar- gins of the gills. Male imago of B. stipposus sp. nov. has yellow upper eyes; each abdo- minal nymph tergite bears apair of contrast light round spots with lightobliquestro- kesi n front of them. Nymph of B. mycetopisBrodsky, 1930, is describedfor the first time.